The Challenge of Cryptocurrency in the Era of the Digital Revolution: A Review of Systematic Literature - Amsyar, Izwan; Christopher, Ethan; Dithi, Arusyi; Khan, Amar Najiv; Maulana, Sabda (Pandawan, 2020)
Money is clearly a primary need of every human being that cannot be avoided, human needs can be realized by using money. Seeing from the lack of systematic literature review papers discussing cryptocurrency, this is a challenge as well as the main purpose of this paper. Along with the development of modernization and globalization which has now entered the industrial era 4.0 revolution there is a blockchain based technology, Cryptocurrency. Cryptocurrency is one of the developments of the blockchain that is often used as a decentralized digital currency. The word Cryptocurrency means a virtual currency that has no physical form, and Cryptocurrency also means that the transaction currency cannot be seen and is safe. This digital currency has many types such as Bitcoin, Ethereum, Litecoin, Monero, and many other types. Although it has no physical form, this currency functions the same as conventional currencies in general and has an exchange rate. Exchange rates on Cryptocurrency fluctuate which means unexpected, this is often exploited by traders. Cryptocurrency transactions in the form of forwarding from one individual to another individual online, therefore they deal directly without a third party. Every technology has advantages and disadvantages aside from efficiency and convenience, Cryptocurrency has the disadvantage of not having the authority responsible for dealing with all problems that occur in all transactions, and money laundering crimes also often occur, this is a challenge for how to utilize Cryptocurrency and blockchain technology in the current era of globalization.